2021
DOI: 10.3389/fbioe.2021.730266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Hydrostatic Pressure on Human Trabecular Bone Regarding Cell Death and Matrix Integrity

Abstract: The reconstruction of critical size bone defects is still clinically challenging. Even though the transplantation of autologous bone is used as gold standard, this therapy is accompanied by donor site morbidities as well as tissue limitations. The alternatively used allografts, which are devitalized due to thermal, chemical or physical processing, often lose their matrix integrity and have diminished biomechanical properties. High Hydrostatic Pressure (HHP) may represent a gentle alternative to already existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…( Figure 4 b). Additionally, the analysis of FAS , FADD , and CASP8 , genes involved in apoptosis [ 30 ] did not show any significant influence of BMP-2 exposure on these processes ( Figure 4 c).…”
Section: Resultsmentioning
confidence: 99%
“…( Figure 4 b). Additionally, the analysis of FAS , FADD , and CASP8 , genes involved in apoptosis [ 30 ] did not show any significant influence of BMP-2 exposure on these processes ( Figure 4 c).…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33] This study aims to prove HHP as an all-encompassing and simplified method in tissue preparation, providing both decontamination and, as shown before, devitalization of bone. 35,47 Considering the few other studies on the major hurdles, as suggested by the varying success rates. 18,37,41 From a biomechanical point of view, an application of up to 600 MPa would be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…29,35 Since apoptotic devitalization is desired in terms of immunological host cell reactions, the selection of pressure levels below 300 MPa is preferable. 20,47 This led to the attempt to optimize the effectiveness of HHP treatment using moderate pressure levels slightly below and slightly above the designated pressure level. Our present study shows that HHP reduced cfu of E. coli despite only using moderate pressure levels of 250 and 350 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…For HHP it was already shown that pressures up to 600 MPa can successfully disinfect bone contaminated with bone specific pathogens 14,45 . However, those pressure levels lead to necrosis of cells, which in turn results in the release of damage associated molecular patterns resulting in the activation of the immune system of the host 20,46 . Therefore, it would be optimal, to develop a process protocol to which cells react primarily apoptotic and a decontaminating effect can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Following an incubation of 5 min, samples were treated as described before and according to manufacturer's manual. 20 RNA was then resuspended in Tris-EDTA-buffer (TE-buffer, pH 7.5) and RNA con- In addition to flow cytometry analysis the supernatants of MSC cultivation were also used for an enzyme linked immunosorbant assay (ELISA) that detects the type I C-terminal collagen propeptide (CICP), which is a by-product of collagen synthesis. Collagen I is secreted as procollagen, which is extracellularly cut at the carboxy-terminal and amino-terminal end into collagen I.…”
Section: Alkaline Phosphatase Activity Measurementsmentioning
confidence: 99%